Development of Thai Handicrafts for Sustainable Community Development Case Study at Mae Tang, Saraphi, Sankampaeng and Mae Rim, Chiang Mai - กิตติพัฒนวิทย์, เจษฎาพล; ศักดิ์สง่า, นภมินทร์; รินแสงปิน, มนัสพันธ์; ไชยนันท์, ไชยเชิด; โอสถาพร, ภควดี (Community and Social Development Journal, 2019)
The development of Thai handicraft to thrive a sustainability in community; case study, four sub-district area in Chiang Mai Province including Mea Tang, Saraphi, Sankampeang, and Mea Rim aims to 1) desire and develop the handicraft products in Chiang Mai and 2) evaluate the satisfaction of the developed handicraft products in four sub-district area. This research had collected many samples of the old style product and their making process under the design knowledge. Then, the research had analyzed and developed products to meet the need of samples group and customers. The research had brought out the outstanding points of products from four groups to develop the new style products and evaluate the satisfaction. From 80 people, most of them, 25 people which equal 31.25%, told that the beauty, color, and tracery of the products are the most important issue. After the process, 248 samples group had evaluated the new handicraft products which had been developed under this research. The research found that in Mea Tang sub-district, the products from Baan Nong Tong community enterprise group had got a high level of satisfaction (mean =4.36, standard deviation =0.15) in Mae Rim sub-district, the products from Pang Luang community enterprise group had got a highest level of satisfaction (mean= 4.50, standard deviation = 0.17)) in Sarapi sub-district, the products from Pa Pong Luang community enterprise group had got a high level of satisfaction (mean = 4.21, standard deviation = 0.13) in San Kam Peang sub-district, the products from San Kam Peang community enterprise group had got a highest level of satisfaction (mean =4.68, standard deviation = 0.09)